Networking-enabled product service system (N-PSS) in collaborative manufacturing platform for mass personalization model. (January 2022) - Zhang, Xianyu; Ming, Xinguo; Bao, Yuguang; Liao, Xiaoqiang; Miao, Rui
Highlights: An overall framework of the integrity and uniformity for N-PSS is proposed. The system and subsystem architecture for N-PSS is proposed. A network model for N-PSS is proposed. It is helpful for enterprises to set up, plan, build and implement N-PSS. It is provide decision-making and reference value for enterprise managers. Abstract: In order to enhance competitiveness, modern enterprises constantly pursue product based innovation, such as the innovation of manufacturing model, service model, and networked collaborative model based on products. Based on these model innovations, this paper is intended for the complex networked product service system, and focuses on the form of network collaboration, organization, mechanism, kernel, etc. The purpose of this paper is to build the comprehensive framework and network model of N-PSS, realize the coordination and value-added of products and services within and outside the company, and improve the efficiency of products and services. Firstly, an integrated collaborative network integrating vertical and horizontal services is constructed, which is helpful to analyze the degree of association, closeness and collaboration of each service item in the whole N-PSS system. Secondly, the system and subsystem architecture of N-PSS proposed in this paper is helpful for enterprises to set up, plan, build and implement product service system for networked collaborative manufacturing. At last, it can empower the product service innovation and digital transformation and upgrading for enterprises, and provide decision-making and reference value for enterprise managers.